Ethnographic approach to EFL/ESL research - Pasassung, Nikolaus (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This article shows that ethnography, as an approach, is a very useful tool to be applied in research attempting a good understanding of EFL/ESL classrooms. With reference to work done by anthropologists and classroom researchers, the present article argues that education, including EFL/ESL classrooms, can be well understood by using ethnographic approaches. This is done by elaborating the relevance of ethnography and the classroom context in the sense that ethnographic principles are applicable in describing and understanding the culture of a classroom, and EFL/ESL teaching in particular.